2021
DOI: 10.1038/s41467-021-23036-9
|View full text |Cite
|
Sign up to set email alerts
|

A SARS-CoV-2 antibody curbs viral nucleocapsid protein-induced complement hyperactivation

Abstract: Although human antibodies elicited by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleocapsid (N) protein are profoundly boosted upon infection, little is known about the function of N-reactive antibodies. Herein, we isolate and profile a panel of 32 N protein-specific monoclonal antibodies (mAbs) from a quick recovery coronavirus disease-19 (COVID-19) convalescent patient who has dominant antibody responses to the SARS-CoV-2 N protein rather than to the SARS-CoV-2 spike (S) protein. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 38 publications
1
63
0
Order By: Relevance
“…Patients with severe COVID-19 showed complement activation and high concentrations of C5a and MAC, suggesting that dysregulation of the complement pathway may participate in CSS and severe COVID-19 complications [ 143 147 ]. Notably, mechanistic studies showed the S or nucleocapsid protein of SARS-CoV-2 can activate the complement pathway [ 148 , 149 ]. Based on the apparent involvement of complement in COVID-19, clinical studies have been initiated for several Abs, including avdoralimab, eculizumab, and vilobelimab (Table 3 ).…”
Section: Therapeutic Absmentioning
confidence: 99%
“…Patients with severe COVID-19 showed complement activation and high concentrations of C5a and MAC, suggesting that dysregulation of the complement pathway may participate in CSS and severe COVID-19 complications [ 143 147 ]. Notably, mechanistic studies showed the S or nucleocapsid protein of SARS-CoV-2 can activate the complement pathway [ 148 , 149 ]. Based on the apparent involvement of complement in COVID-19, clinical studies have been initiated for several Abs, including avdoralimab, eculizumab, and vilobelimab (Table 3 ).…”
Section: Therapeutic Absmentioning
confidence: 99%
“…Several neutralizing antibodies targeting the RBD of S protein are being analyzed and evaluated clinically [ 11 , 12 ]. The N terminal-domain (NTD) of S protein also contains immunoprotective epitopes, the most immunodominant of which elicits the production of antibody 4A8, a mAb with high neutralizing potency against the NTD of SARS-CoV-2 [ 13 , 14 ].…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…Antibodies targeting the viral nucleocapsid (N) protein—which may mediate viral genome expression and assembly—have been isolated from convalescent sera of COVID-19 patients in the early recovery phase; in contrast, anti-S protein antibodies dominate late-phase sera [ 14 , 22 , 23 ]. A recent study highlighted a particular anti-N-protein nAb, nCoV396, which inhibited N-protein–MASP-2 interaction [ 14 ], thus blocking N-protein-mediated complement hyperactivation and combatting the pro-inflammatory state characterizing COVID-19 [ 14 ]. Further work is required to elucidate the full prophylactic and therapeutic potential of these Abs.…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%
“…Most recently, Ma et al showed that NP binds the Gasdermin D linker region and hinders Gasdermin D cleavage by caspase-1 in monocytes, leading to the inhibition of host cell pyroptosis [9]. Kang et al isolated a high-affinity anti-NP mAb from a convalescent COVID-19 patient and found that the binding of the mAb to the RBD of NP compromised the induction of complement hyperactivation by NP, a risk factor for the morbidity and mortality of COVID-19 patients [10]. Interestingly, viral NP and the RNA genome are detectable in blood specimens of SARS-CoV-2-infected patients, and the levels correlate with mortality in COVID-19 ICU patients [11,12].…”
Section: Introductionmentioning
confidence: 99%